Studies and Characterization of Mixed Ligand Complexes of Aluminium with (N— O) and (N— S) Donor Ligands - Gothwal, Y.K.; Joshi, Jyoti; S. Joshi, Bidya (Asian Journal of Chemistry, 2010)
The synthesis of some aluminium(III) mixed ligand complexes Having donor Schiffs bases, N-phenylsalicylaldimine (SLIMH) and 3-(phenylamino)-1-phenyl-2-butene-1-one (BZAMH), with 3-aryl-2-mercapto-4(3H)quinazolones (MAQH) has been reported. The mixed ligand complexes were obtained by the reaction of (Schiffs base)2 aluminium isopropoxy precursors with the mercapto ligands. The complexes were characterized by elemental analysis and spectral studies. The studies reveal the formation of hexacoordinate complexes with bonding of the mercapto ligands.